Infection of Aedes mosquitoes by native Wolbachia in urban cemeteries of Southern Mexico - Jorge Aurelio Torres-Monzón; Mauricio Casas-Martínez; Teresa López-Ordónez (Instituto Nacional de Salud Pública, 2020)
Objective. To evaluate the prevalence of Wolbachia infections in Aedes spp. field populations from cemeteries of Southern Mexico. Materials and methods. Six cemeteries were selected to be sampled in the central part of the Soconusco region, Chiapas. Aedes albopictus and Ae. aegypti mosquitoes were collected during the rainy season of 2015. Females were analyzed individually by PCR to determine the presence of Wolbachia. Results. A field overall prevalence of 38% was found; only Ae. albopictus mosquitoes were positive. Conclusion. Local strains of Wolbachia were detected and have the potential to be applied as a biological method for vector control.